Imaging of the mean frequency of the ultrasonic echoes - Klimonda, Ziemowit; Nowicki, Andrzej (Archives of Acoustics, 2007)
A standard USG image is in fact a visualization of a distribution of the reflexion coefficients.There is an increasing interest in imaging of the different parameters, which mightcharacterize another physical properties of a tissue. The attenuation coefficient is one of suchparameters and theoretically it can be estimated using frequency shift of the RF signal. The frequencyshift results from dispersive character of the attenuation in tissue and is a function ofattenuation along the propagate path. In this work authors use echo’s mean frequency as animaging modality. The results of measurement of tissue phantom using 10 MHz linear arrayare presented. The preliminary results are encouraging being the first attempt towards mappingof the attenuation in tissue.